EVALUATION OF PRESERVED ORGANS OF PLASTINATION WITH THE DEHYDRATION PHASE AT ROOM TEMPERATURE - Ni Nyoman Werdi Susari; I Nengah Wandia; I Ketut Suatha; Luh Gde Sri Surya Heryani (Buletin Veteriner Udayana, 2024)
Organ preservation is an effort to maintain the integrity of organs for a long time by preventing further damage and decay processes. Plastination is an organ preservation process by inserting polymer materials to maintain the shape and composition of the organ. This research aims to evaluate the product of a plastination technique carried out using generic chemicals in the community and equipment. The organs used in this plastination process are heart, brain and lungs from the bali cattle. The research materials and tools needed are distilled water, formalin, acetone, liquid silicone rubber, silicon catalyst, 10 ml syringe, plastic bag/tub with lid, vacuum chamber, plastic bucket/tub without lid, and hardening room/box. The vacuum chamber is made from a modified drum so that it can accommodate cadaver plastination (large size). The plastination technique is carried out in four main stages, one of which is the dehydration phase with acetone which is carried out at room temperature. The plastinated organs that are the product of this technique will be evaluated for their flexibility, color, and odor. The results of this research produce plastinated organs that have a stiff texture, pale color, and a non-pungent odor. From the research results obtained, it can be suggested that it needs to be stored in a vacuum for longer (for 1 week) so that the texture can resemble its original shape.